2008
DOI: 10.1182/blood-2008-02-138933
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 protein expression and basal activation of Erk in vivo in follicular lymphoma

Abstract: IntroductionFollicular lymphoma (FL) is a non-Hodgkin lymphoma of germinal center B-cell origin. FL is the second most common nonHodgkin lymphoma and represents 20% of all lymphomas in the adult population. 1 Although the course of disease is indolent, it is largely incurable, with a median survival of 7 to 10 years. With time, FL typically transforms into a high-grade lymphoma. FL is characterized by the t(14;18) (q32;q21) translocation, 2-4 which leads to constitutive expression of the antiapoptotic Bcl-2 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 56 publications
2
52
0
Order By: Relevance
“…Involvement of IL4 in follicular lymphoma pathogenesis has been recently reported, along with Erk and STAT6 activation. 21 However, we could not correlate expression of the immunoglobulin E receptor CD23, a STAT6 target, by tumor cells, with IL4I1 expression (data not shown). In cHL and follicular lymphoma, IL4I1 might thus be induced by other signals in addition to the IL4/IL13/ STAT6 pathway.…”
Section: Resultsmentioning
confidence: 80%
“…Involvement of IL4 in follicular lymphoma pathogenesis has been recently reported, along with Erk and STAT6 activation. 21 However, we could not correlate expression of the immunoglobulin E receptor CD23, a STAT6 target, by tumor cells, with IL4I1 expression (data not shown). In cHL and follicular lymphoma, IL4I1 might thus be induced by other signals in addition to the IL4/IL13/ STAT6 pathway.…”
Section: Resultsmentioning
confidence: 80%
“…IL-4 has been reported to be elevated in FL with downstream phosphorylation of Erk and activation of Mek. 38 Gene expression profiling has made inroads by demonstrating activation of IL-4-dependent activation of STAT6 in FL B cells and T-helper cells in the tumor microenvironment indicating an interdependent axis. 39 IL-10 and Leptin have been associated with FL development and result in immune suppression.…”
Section: Discussionmentioning
confidence: 99%
“…4 Additional molecular lesions or secondary hits are required to cooperate with BCL2 in the evolution of the malignant phenotype, although the precise mechanisms of lymphomagenesis remain to be elucidated. Gene expression profile studies of FL further suggest that the lymph node microenvironment may play a role in the biology of FL through tumor infiltrating T cells and macrophages, [5][6][7][8][9] possibly involving cytokines 10,11 or other immunomodulatory mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that IL-4 protein is increased, and MAPK1 is activated in FL, as determined by multiplex cytokine ELISA arrays and reverse-phase protein arrays. 11 One recent study identified the source of increased IL-4 expression in FL as tumor-infiltrating T helper cells, with the consequence of over-expression of IL-4-regulated genes in FL tumor cells via activation of STAT6. 10 In our current study, we found increased expression of IL4R, MAPK1 and AKT transcripts in enriched sorted FL tumor cells, further indicating that IL4/IL4R, MAPK and PI-3K/AKT pathways potentially play crucial roles in FL tumor proliferation and survival.…”
mentioning
confidence: 99%